Antitumor activity of mixing gemcitabine with pravastatin in a microemulsion against a549 non-small cell lung cancer cells. - MAYSON H. ALKHATIB; SHARIFA M. THEEBAN; WADIAH S. BACKER (International Journal of Pharma and Bio Sciences, 2017)
Combining several anticancer drugs in a nanoparticle is a new promising regimen in cancer therapy. In this study, the antimetabolite agent, gemcitabine (GEM), was combined with the cholesterol lowering drug, pravastatin (PRVA), in a microemulsion (ME) formula. The cytotoxicities and apoptotic effects of the combination formulas were in vitro evaluated in A549 non-small cell lung cancer cells. The cytotoxicity was assessed through using 3 (4,5dimethylthiazole-2-yl)-2,5-diphyneltetrazolium bromide (MTT) assay, while the mechanism of cell death was evaluated by observing the morphological changes of the treated cells under light microscope, and detecting apoptosis by using ApopNexin apoptosis detection kit and 4′,6-diamidino-2-phenylindole (DAPI) dye. It has been found that a 5µM of mixed GEM and PRVA at a ratio of 2:1, respectively, in ME (2GEM/PRVA-ME) has the best cytotoxic and apoptotic effect on the A549 cells.This study suggests that combining GEM with PRVA in a ME formula has a great therapeutic effect on A549 cells.